How to keep well in wartime - Great Britain. Ministry of Health ; Central Council for Health Education (Great Britain); Clegg, Hugh Anthony, 1900- (London : His Majesty's Stationery Office, 1943)
1943 1943 1940s 28 pages : illustrations HELP YOURSELF TO BE WELL not fulfil their heroic task with minds and bodies that were untrained. To get the most out of life you must put the most into it. To live, to love, to laugh, to labour to the fullness of your capacity, get fit and keep fit. Remember, too, that good health is not just something the young have. Each period of life has its standard of good health. The health of old age is ripeness, mellowness. The health of youth is energetic and expansive. Whatever your age, strive for the best health available to you. Seek Health with Eagerness. The average man wants a job he is interested in, to be decently paid for it, to have a wife and family, friends, hobbies, and leisure in which to enjoy them. These, in their different mixtures, bring him happiness. Happiness, satisfaction, is what he aims at. Without good health full happiness cannot be obtained. If you want to reach happiness, to be complete, seek health with the eagerness with which so many foolish men have sought gold. Good health is the real riches: it is up to you to get it and to keep it. The pursuit of good health can be an adventure. And in this adventure all the doctors and the health services in the country are there to help you. Don't think you are too old to begin. In this war we have all decided that this country is worth dying for if need be. It is also worth living for and working for, and to do this to the top of your bent you must be as fit as you can. And just how fit you can become you probably haven't yet found out. 23 420/BS/7/16/18